The Corey-Seebach Reagent in the 21st Century: A Review - Muhammad Haroon; Ameer Fawad Zahoor; Sajjad Ahmad; Asim Mansha; Muhammad Irfan; Aqsa Mushtaq; Rabia Akhtar; Ali Irfan; Katarzyna Kotwica-Mojzych; Mariusz Mojzych (Molecules, 2023)
The Corey-Seebach reagent plays an important role in organic synthesis because of its broad synthetic applications. The Corey-Seebach reagent is formed by the reaction of an aldehyde or a ketone with 1,3-propane-dithiol under acidic conditions, followed by deprotonation with n-butyllithium. A large variety of natural products (alkaloids, terpenoids, and polyketides) can be accessed successfully by utilizing this reagent. This review article focuses on the recent contributions (post-2006) of the Corey-Seebach reagent towards the total synthesis of natural products such as alkaloids (lycoplanine A, diterpenoid alkaloids, etc.), terpenoids (bisnorditerpene, totarol, etc.), polyketide (ambruticin J, biakamides, etc.), and heterocycles such as rodocaine and substituted pyridines, as well and their applications towards important organic synthesis.